The Effect of Payload Weight to Mean Coil Diameter of Helical Compression Spring for Payload Separation - Laksono , Shandi Prio (BRIN Publishing, 2021)
Weight is one of major factors in sounding rocket or launch vehicle design. Indeed, payload weight contributes to the rocket weight. Sounding rocket release the payload in the upper atmosphere at the certain altitude. Sounding rocket is intended to carry the payload as much as possible. In payload jettison/separation system, helical compression spring is commonly used. The previous study result show that in order to avoid mechanical failure of the spring, if the payload weight was 60 kg, the minimum wire diameter of helical compression spring must be 8 mm with mean coil diameter of 80-96 mm. Based on the previous study result, this study investigated the effect of payload weight to mean coil diameter of helical compression spring for payload separation. The numerical method was used in this study. In order to increase the payload weight, the mean coil diameter must be decreased. The results obtained show that the maximum payload weight that can be used was 77 kg with the maximum mean coil diameter of 80 mm, and free length of 0.417 m. In addition, safety factor of 1.65 and energy storing of 81.8 N.m was obtained.